"Every year they ignore us": public school closures and public trust. (15th March 2021) - Nuamah, Sally A.
ABSTRACT: How do citizens' experiences with public schools shape their feelings about politics? Over the past two decades, public schools have closed at an increasing rate across the United States. In 2013, US history was made in Chicago, Illinois, when the most public schools in a single year were closed. Despite the large number of school closures nationwide, there is a little research on what citizens think about them and their potential political effects. Utilizing qualitative data from community meeting transcripts, ethnographic observations, and interviews related to the historic school closures by Chicago Public Schools, this paper reveals that the inconsistencies experienced by citizens affected by school closures contribute to distrust of the real objectives behind the policy. Citizens' mistrust of the policy, likely shapes negative perceptions of the policy implementers and politics, at large. This paper has important implications for studies that seek to understand how and why citizens oppose policies that are framed as advantageous to them. Additionally, this paper provides significant insights into the ways in which citizen engagement with educational policies can act as a process of political learning, specifically related to public trust.